2014
DOI: 10.1111/cxo.12099
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary macroadenoma: a case report and review

Abstract: Pituitary adenomas are the most common tumours of the sellar region. They generally have a slow but severe impact on vision due to compression of the optic nerves, optic chiasm and cavernous sinus. This case report reviews the clinical presentation, management and treatment of the major classifications of pituitary adenoma. As Australian optometrists perform over 300,000 visual field assessments per year, it is vital they are aware of this important cause of visual field loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 70 publications
0
6
0
5
Order By: Relevance
“…Four to six millimetres of chiasmal elevation is needed to produce visual field defects. A more detailed study found that 6.3 mm of chiasmal elevation was required to induce visual field defects in 50 per cent of patients and an additional 5.0 mm is needed to increase the frequency to 90 per cent [5]. In this case, although the MRI showed the pituitary tumour impinges on the optic chiasma, but patient did not show any visual defects.…”
Section: Discussionmentioning
confidence: 70%
“…Four to six millimetres of chiasmal elevation is needed to produce visual field defects. A more detailed study found that 6.3 mm of chiasmal elevation was required to induce visual field defects in 50 per cent of patients and an additional 5.0 mm is needed to increase the frequency to 90 per cent [5]. In this case, although the MRI showed the pituitary tumour impinges on the optic chiasma, but patient did not show any visual defects.…”
Section: Discussionmentioning
confidence: 70%
“…[147][148][149] Chiasmal defects are characteristically bitemporal (Figure 8), with a bias toward either superior (for example, pituitary adenoma) or inferior (for example, craniopharyngioma) bitemporal defects, depending on aetiology. 146,150 Visual field losses in the far superotemporal and inferotemporal regions of the field may at first be subtle and the wider and symmetrical 30-2 test grid may be required.…”
Section: Beyond the Retina And Optic Nervementioning
confidence: 99%
“…Pa cien tai ga li il gai nepa ste bë ti po ky èiø ir jaus tis ge rai [13]. Daþ niau siai skundþia ma si gal vos skaus mais (23-48 %) ir re gos su tri ki mais (37-100 %), la bai re tai aug lys pa si reið kia trau ku liais, ri norë ja ar hi po fi zës apo plek si ja [10,44]. Gal vos skaus mà, kuris ne pri klau so nuo na vi ko dy dþio, su ke lia kie tø jø dan ga lø tem pi mas [45].…”
Section: Klinika Ir Diagnostikaunclassified
“…Re gos su tri ki mai, prie ðin gai, pri klau so nuo na vi ko dy dþio ir au gi mo kryp ties -HA ga li spaus ti re gos ner vø kryþ mae, gal vi nius ner vus (akies ju di na mà já, skri dini ná, ati trau kia mà já) [10,44]. Daþ niau si re gos simp to mai: bi tem po ra li në he mia nop si ja (54-69 %), ki ti aki plo èio sutri ki mai (85 %), su ma þë jaes re gos aðt ru mas (42-88 %) [10,44,46].…”
Section: Klinika Ir Diagnostikaunclassified
See 1 more Smart Citation